EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI TIPE PICTORIAL RIDDLE DENGAN KONTEN INTEGRASI- INTERKONEKSI PADA MATERI SUHU DAN KALOR TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Joko Purwanto; Binti Uswatun Hasanah (Kaunia: Integration and Interconnection Islam and Science, 2014)
This research intents on knowing: (1) the effectivity of inquiry learning model pictorial riddle type with integration-interconnection content toward critical thinking skill of students on heat and temperature material. (2) the increasing of critical thinking skill of the students who join the lesson using inquiry model pictorial riddle type with integration-interconnection content on heat and temperature material. The research used a quasi experimental with pretest-posttest control group design. The population were the tenth grade students of SMA N 1 Piyungan years 2013/2014. The subject of the study are class XC and XD which chosed by purposive sampling technique. Instrument to examine critical thinking skill of the student was essay questions. Data was collected by test and analyzed using descriptive statistics and normalized gain (N-gain). The results  showed  that:  (1)  there  is  possitive  effect  between  inquiry  learning  model pictorial riddle type with integration-interconnection content toward critical thinking skill of students on heat and temperature material. (2) the increasing of critical thinking skill of the students who join the lesson with inquiry learning model pictorial riddle type with integration-interconnection content on heat and temperature material is hingher than control class with average posttest score 60,65 and  N-Gain 0,316.